Literature Review: Hubungan Struktural Self-Efficacy, Self-Regulation, Social Shared Metacognition Terhadap Kemampuan Pemecahan Masalah Statistika Kolaboratif Siswa SMP - Jusfita Jusfita; Aisyah Nursyam (Mathematics Education Study Program, 2025)
This study is a literature review that aims to analyze the structural relationship between self-efficacy, self-regulation, and social shared metacognition on students’ collaborative statistical problem-solving abilities at the junior high school level. The review highlights the importance of students’ confidence, self-directed learning management, and shared metacognitive awareness in supporting successful collaborative learning. Self-efficacy strengthens students’ belief and motivation, self-regulation guides independent learning strategies, while social shared metacognition enhances group coordination and reflection. The results indicate that these three variables interact and contribute positively to improving students’ collaborative statistical problem-solving skills. The findings emphasize the need to integrate affective, cognitive, and social aspects in mathematics learning to develop students’ critical and collaborative thinking abilities.